MicroRNA-193-3p attenuates myocardial injury of mice with sepsis via STAT3/HMGB1 axis - Pan, Jianyuan; Buse, Alexandra; Dorn, Dennis; Chiristine, Bettina; Christoph, Laeuf Ilona Mariya; Tang, Yongqin (Journal of translational medicine, 2021)
Little is known regarding the functional role of microRNA-193-3p (miR-193-3p) in sepsis. Hence, the aim of the present study was to investigate the effect of miR-193-3p on myocardial injury in mice with sepsis and its mechanism through the regulation of signal transducers and activators of transcription 3 (STAT3).
Der Artikel wurde am 31.10.2024 zurückgezogen
Gesehen am 03.08.2023